Digital Marketing Improvement to Achieve Awareness and Better Engagement for Holybags - Raisy; Fahlevi, Renza; Sinambela, Fitriana Aidnilla (Jurnal Pengabdian Masyarakat, 2024)
Purpose: The study provides insight on the importance of Digital Marketing and its evolution which sees business today keep up eith the latest trends and explore new ways to promote products or services and achieve virality via social media deemed beneficial for business. Method: Qualitative methodology consist of observation, interviews, and direct involvement, was used during the consideration for social media optimization to facilitate Digital Marketing, which pertains to its aptness to closely enhance productivity. Practical Applications: This study presents how Digital Marketing through modern social media platforms can boost a reach, engagement, and consumer intention to make a purchase, thereby improving a business’s prospects moving forward. Findings from this study also indicate the potential advantages for businesses from parallel sectors. Conclusion: This study brings to light how prevalent Digital Marketing through social media has become in the modern age and how cost-effective and beneficial it can be for businesses looking to promote their products or services. Adopting current Digital Marketing strategies is crucial to connecting with the modern-day consumer and to establish a brand’s position in the market.